Critical Success Factors In the Implementation of Strategy by the Multinational Corporations in the Pharmaceutical Industry: An Empirical Investigation - Awino, Zachary Bolo (Archives of Business Research, 2016)
Strategy implementation is the key that opens doors to creatively align organizational strategy with its internal support systems that transforms analyzed and formulated strategies into action. An organization in the pharmaceutical business, which is a business that competes in the knowledge economy for discovering and commercializing therapeutic agents, must endeavour to continually develop strategies to protect its intellectual capital and improve performance. Despite this realisation the importance of strategy implementation, is still greatly overshadowed by a focus on the strategy formulation process. Literature available on strategy implementation is very scarce and especially in the pharmaceutical industry. This study, therefore, is poised to explore and determine the critical success factors for strategy implementation among Multinational corporations in the Kenyan pharmaceutical industry. The study was conducted in Kenya in 2014 as a census survey of twelve Multinational pharmaceutical corporations. Data for this survey was collected through the use of structured questionnaires, which were distributed to 36 respondents of which 32 responded an 89% respondent rate. This study was hinged on the dynamics capabilities theory, resource based view theory and the concept of competitive advantage. Data analysis was done using descriptive statistics and factor analysis to a large extent. Results indicate that critical success factors for strategy implementation include; Infrastructure factors; Clear and concise communication of the strategy to the staff, with a variance loading of(0.942)Resource set aside for new strategy,(0.871,variance loading),Planning, co-ordinating, monitoring and delegation of responsibilities for implementation of strategy,(0.970), Organisational structure that is supportive(0.889).Time frame; Specified time frame allocated for strategy implementation(0.971), allocation for obstacles surfaced during implementation that were not envisioned beforehand, environmental factors also emerged as key to this process. For competitive advantage. People-product mix; Possession of detailed knowledge on customers' needs, tastes and preferences by employees, hiring and retraining top talent within the organization, continuous product improvement and innovations, Production of unique products for a specific target market, partnering with customers to produce highly customized products and strategic alliances with key stakeholders in the industry. These factors had implication on theory and practice since they were found to be universal.